MENINJAU PENERAPAN INSENTIF PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) UNTUK GREEN BUILDING: STUDI KASUS KOTA BANDUNG - Septiana, Rhama Aulia; Elvinna, Dina; Aprilia, Nabila; Arkananta, Rajwa Ryanda; Mondong, Juandinho Dwantara Yosua (Jurnal Akuntansi dan Pajak, 2024)
The implementation of the green building concept is believed to be one of the solutions to reducing emissions caused by environmentally unfriendly construction. Green building incentives in the PBB-P2 sector can serve as an effective policy alternative to encourage public interest in constructing environmentally oriented buildings. To examine the policies and implementation of these incentives in Indonesia, this study focuses on analyzing the policies and application of PBB-P2 incentives for green buildings in Bandung City and reviewing green building tax incentives in other countries as benchmarks for implementing green building initiatives in Indonesia. Research findings reveal that the implementation of the Property and Urban/Rural Land Tax (PBB-P2) incentives for green buildings in Bandung City has not been optimal. Key challenges include limited public awareness, unclear regulations, and low public interest in green buildings. The government needs to periodically evaluate the implementation of tax incentive policies, enhance public awareness campaigns on PBB-P2 incentives, establish clear incentive durations, and foster collaborations between the government and the private sector to support green buildings through incentive programs such as low-interest rates and ecolabeling. These efforts aim to improve the quality of the policy framework.